2009
DOI: 10.3989/gya.130908
|View full text |Cite
|
Sign up to set email alerts
|

Dry cured ham quality as related to lipid quality of raw material and lipid changes during processing: a review.

Abstract: SUMMARYDry cured ham quality as related to lipid quality of raw material and lipid changes during processing: a review.Lipids play a key role in sensory traits of dry cured hams. Both the quantity and the composition of lipids in raw material affect dry-cured hams quality. The lipid characteristics strongly depend on rearing systems developed in different area in Europe. During processing, lipids undergo lipolysis and oxidation. Phospholipids are the main substrates of both lipolysis and oxidation. Lipolysis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 52 publications
3
32
0
3
Order By: Relevance
“…They have more adipose tissues thickness and more intramuscular fat (Tejeda et al, 2002;Gandemer, 2009). The differences in IMF are mainly due to higher triglyceride accumulation while the polar lipid fraction is similar between traditional and industrial genotypes of pigs.…”
Section: Effect Of Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…They have more adipose tissues thickness and more intramuscular fat (Tejeda et al, 2002;Gandemer, 2009). The differences in IMF are mainly due to higher triglyceride accumulation while the polar lipid fraction is similar between traditional and industrial genotypes of pigs.…”
Section: Effect Of Genotypementioning
confidence: 99%
“…The differences in IMF are mainly due to higher triglyceride accumulation while the polar lipid fraction is similar between traditional and industrial genotypes of pigs. According to Gandemer (2009) this fact is due to the fact that traditional pigs have a low capacity to deposit muscles in carcass and deposit a large amount of the feed energy as fat in both adipose and intramuscular depots.…”
Section: Effect Of Genotypementioning
confidence: 99%
“…A recent research of Estany et al (2014) has shown that a haplotype in the promoter region of the stearoyl-CoA desaturase (SCD) gene, which enhances fat desaturation and, as a result, MUFA and oleic acid in muscle and subcutaneous fat, segregates in Duroc. This beneficial effect is maintained in purebred dry-cured Duroc hams (Henriquez-Rodriguez et al, 2015), despite the fatty acid compositional changes occurring through lipolysis and oxidation in the curing process (Narváez-Rivas et al, 2008;Gandemer, 2009). …”
Section: Isolation Of Genomic Dna and Genotypingmentioning
confidence: 99%
“…The intramuscular fat content (IMF) and fatty acid (FA) composition, especially the monounsaturated fatty acid (MUFA) content, influence the final quality of the dry-cured products, since they affect color, aspect and texture of ham slices, as well as the intensity and persistence of aroma (Ruiz-Carrascal et al, 2000;Gandemer, 2009;Lorido et al, 2015). Moreover, the consumption of dietary MUFA promotes healthy blood lipid profiles, mediates blood pressure, improves insulin sensitivity and regulates glucose levels (Gillingham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Official Quality standard eliminated this technique for the classification of carcasses (B.O.E., 2007a), but in practice, it is a method that is still used by the industrial sector, because the composition of the intramuscular fat from meat plays a decisive role in the drycured process of the quality parts and determines, for example, the number of days required for the salting and drying of hams (Cava and Andres, 2001). It also influences the consistency, color and fat oxidation, which are decisive factors in the quality of the meat, both fresh and drycured (Melgar et al, 1991;Ruiz et al, 2000;Ventanas et al, 2006;Ventanas et al, 1999;Gilles, 2009).…”
Section: Introductionmentioning
confidence: 99%